Economic-geographical approach for developing small and medium businesses in central Kazakhstan - Chistyakova, G.N.; Huzsti, Zh.; Chistova, A.A. (Pub.KarSU, 2016)
This article defines the specific tasks for the development of small and medium businesses (SMB) in the specific conditions of Central Kazakhstan and projectedthe priority development of the cities of two levels. These cities can become Karaganda, Temirtau, Zhezkazgan, Satpayev, Balkhash.Enhancing the role of small and medium businesses (SMB) in Central Kazakhstan requires the study of world experience and search of the most suitable economic -geographical approaches to solving the problems of development and the territorial organization of the considered sector of the economy. In this regard, the authors consider that the proposed economic-geographical approaches to socio-economic development of the region in conjunction with eco- nomic and geographic conditions will bring SMB on the trajectory of substantiated development, which meets the standards of medium and highly developed countries.Conducted workconfirms the relevance of the research results of the economic potential of Central Kazakhstan’s to develop the Concept of small and medi- um businesses development, since the spatial organization of the territory turns into a major factor of social and economic development. Мақалада орталық Қазақстанның спецификалық жағдайында шағын жəне орта бизнестің (ШОБ) дамуына арналған нақты міндеттері анықталып, екі деңгейлі қалалардың даму артықшылықтары болжанды. Ондай қалаларға Қарағанды, Теміртау, Жезқазған, Сəтпаев, Балқаш жатқызылды. Орталық Қазақстандағы ШОБ-тың алатын орнын көтеру үшін əлемдік тəжірибе мен ізденістерді зерттеп, қарастырылып отырған экономика секторын аумақтық ұйымдастырудың жəне дамудың экономикалық-географиялық басымды тəсілдемелерін іздеуді қажет етеді. Осыған орай авторлар зерттеп отырған аймақтың əлеуметтік экономикалық дамуымен ұштасатын экономикалық- географиялық жағдайларды ескеретін, ШОБ-ның əлемдегі орта жəне аса дамыған елдердің стандартына сəйкес келетін негізделген траекторияға шығатын экономикалық-географиялық тəсілдемелер ұсынады. Жүргізілген жұмыстар Орталық Қазақстанның экономикалық əлеуетінің дамуына экономикалық зерттеулердің нəтижелерінің аймақта шағын жəне орта бизнесті дамытудың қажеттілігін растайды, себебі аумақтың кеңістіктегі ұйымдастырылуы əлеуметтік-экономикалық дамуында маңызды факторға айналады. В статье определены конкретные задачи для развития малого и среднего бизнеса (МСБ) в специфических условиях Центрального Казахстана и спрогнозировано приоритетное развитие городов двух уровней. Такими городами могут стать Караганда, Темиртау, Жезказган, Сатпаев, Балхаш. Повышение роли МСБ в Центральном Казахстане требует изучения мирового опыта и поиска наиболее приемлемых экономико-географических подходов в решении проблем развития и территориальной организации рассматриваемого сектора экономики. В связи с этим авторы считают, что предлагаемые экономико-географические подходы социально-экономического развития региона в сочетании с экономико-географическими условиями позволят вывести МСБ на траекторию обоснованного развития, соответствующего стандартам средне- и высокоразвитых стран мира. Проведенная работа подтверждает востребованность результатов исследования экономического потенциала Центрального Казахстана для разработки экономико-географических подходов к развитию малого и среднего бизнеса региона,так как пространственная организация территории превращается в важнейший фактор социально-экономического развития.
Орталық Қазақстанда шағын жəне орта бизнесті дамытудың экономикалық-географиялық тəсілдемесі
Экономико-географический подход к развитию малого и среднего бизнеса в Центральном Казахстане
Keywords: Central Kazakhstan; small and medium business; spatial organization of the territory; the interna-tional division of labor; growth poles; regional cluster; territorial-economic system; economic macro-region; economic specialization; innovation and industrial development; polarized development; the Central Asian region; polycentric development; small and medium-sized cities; market economy